2022
DOI: 10.1140/epjds/s13688-022-00320-2
|View full text |Cite
|
Sign up to set email alerts
|

Tainted ties: the structure and dynamics of corruption networks extracted from deferred prosecution agreements

Abstract: Corruption, bribery, and white-collar crime are inherently relational phenomena as actors involved in them exchange information, resources, and favours. These exchanges give rise to a network in which the actors are embedded. While this has been often emphasized in the literature, there is a lack of studies actually empirically examining the structural properties of corruption networks. We aim to fill this gap with this exploratory study analysing the networks of corporate and public sector bribery. We theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Situated in the context of previous research, this data can thus contribute to the research on corruption networks and the way they operate (Lauchs et al, 2011;Diviák et al, 2019;Luna-Pla and Nicolás-Carlock, 2020;Wachs et al, 2020). Exploratory probe into three of the network extracted here reveals remarkable structural similarities in the centralization of their structures despite the differences in the sizes of the networks or their time span (Diviák and Lord, 2022). In terms of methodological research, our data collection framework may be further extended to other sources of textual data and it may also be automated using available methods for automated text analysis (natural language processing methods).…”
Section: Discussionmentioning
confidence: 99%
“…Situated in the context of previous research, this data can thus contribute to the research on corruption networks and the way they operate (Lauchs et al, 2011;Diviák et al, 2019;Luna-Pla and Nicolás-Carlock, 2020;Wachs et al, 2020). Exploratory probe into three of the network extracted here reveals remarkable structural similarities in the centralization of their structures despite the differences in the sizes of the networks or their time span (Diviák and Lord, 2022). In terms of methodological research, our data collection framework may be further extended to other sources of textual data and it may also be automated using available methods for automated text analysis (natural language processing methods).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, our data does not contain information about undetected or unsolved cases of criminality. This is a common limitation in data-driven studies of criminal behavior, which by nature are limited to prosecuted or highly visible activities 69 . At the same time, events in our data are when individuals are charged with crimes - not all events are correctly assigned to the guilty individual.…”
Section: Discussionmentioning
confidence: 99%
“…To begin with, there is a rich tradition of case studies on corruption, which are common within fields such as sociology, criminology, organisational research, and anthropology, and these provide pivotal building blocks for the formation of a theoretical base to better understand corruption (e.g., Diviák and Lord 2022;Slingerland 2018;Brooks 2016). While case studies are extremely important for understanding the mechanisms behind corruption, one limitation is that they are restricted to forms of corruption that have already been exposed and where detailed information is already available.…”
Section: Methodological Considerations Traditional Approaches To Stud...mentioning
confidence: 99%
“…Corruption in real-world settings is rarely observed directly, and traditional corruption measures are typically operationalised at the macro rather than the micro level. That said, promising examples of recent corruption research which have succeeded in drawing such micro-macro links are found in the fields of network science, complexity science, and computational social science (e.g., Diviák and Lord 2022;Villamil et al 2022;Granados and Nicolás-Carlock 2021). The prerequisite and key to this development is the availability of large-scale data with a high level of granularity based on observations at the micro level.…”
Section: Corruption Research and Analytical Sociologymentioning
confidence: 99%